Pulmonary tuberculosis and venous thromboembolism - kambouche, faouzia; Mohamed El Habib , Labdouni (International Journal of Medicine, 2024)
Acute infections are among the risk factors for venous thromboembolism (VTE). The role of chronic infections such as active tuberculosis is poorly defined, although several case reports and case series have suggested a link association between tuberculosis and VTE. The unexpected resurgence of tuberculosis (TB) in developed countries provided the rationale for evaluating VTE as a possible complication of TB; never theless, the topic has received little attention in the literature.Patient and Method: This is a prospective multicenter study done between January 2016 and January 2018. It is about 17 cases of confirmed pulmonary tuberculosis associated with deep vein thrombosis.Results: It is about fifteen men and two women, their average age is 44,88 years. The thromboembolic complication revealed tuberculosis among 2patients, appearing during the hospitalization of 15 patients among which 11of them receiving antituberculosis drug. We have listed 3 cases of immediate pulmonary embolism and 14cases of deep vein thrombosis complicated with pulmonary embolism in 7 cases. These patients received anti-tuberculosis treatment according to the 2RHZE / 4RH protocol and a curative anticoagulant treatment based on low molecular weight heparin. A relay by vitamin K antagonists was instituted after a satisfactory INR control. The average time to effective anticoagulation was 15.12 days with extremes between 08 and 50 days.There was favorable evolution among 14 patients, 1of them was lost to follow-up. Sight and the evolution has been fatal in two case.Conclusion: Thromboembolic (DVT) disease must be sought systematically in the TB patients because of the risk of this complication particularly in extensive and severe forms. Prophylactic anticoagulation therapy finds its indications in these forms.